Quantum Systems in Physics, Chemistry, and Biology Advances in Concepts and Applications - Tadjer, Alia.; Pavlov, Rossen; Maruani, Jean.; Brändas, Erkki J.; Delgado-Barrio, Gerardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book reviews the most significant developments in quantum methodology applied to a broad variety of problems in chemistry, physics, and biology. In particular, it discusses atomic and molecular structure, dynamics and spectroscopy as well as applications of quantum theory to biological and condensed matter systems. The volume contains twenty-four selected, peer-reviewed contributions based on the presentations given at the Twentieth International Workshop on Quantum Systems in Chemistry, Physics, and Biology (QSCP-XX), held in Varna, Bulgaria, in September 2015. It is divided into five sections containing the most relevant papers written by leading experts in the fields. This book will appeal to advanced graduate students, researchers, and academics involved in theoretical, quantum or statistical and computational chemical physics and physical chemistry.
Quantum Methodology -- Structure and Dynamics -- Atomic and Molecular Properties -- Biochemistry and Biophysics -- Fundamental Theory.
Keywords: Chemistry, Physical and theoretical; Quantum physics; Bioinformatics; Nanotechnology; Physical chemistry; Theoretical Chemistry; Quantum Physics; Computational and Systems Biology; Nanotechnology; Physical Chemistry